Integrated Approaches for Management of Phytophthora Blight in Sesame (Sesamum indicum L.) - Prasad, Durga; Singh, Shwetank; Upadhyay, Utkarsh (International Journal of Economic Plants, 2023)
The present investigation was conducted in the experimental field of Banda University of Agriculture and Technology, Banda, Uttar Pradesh, India during July to October of 2021. Phytophthora blight caused by Phytophthora parasitica var. sesame is prevalent in all the sesame grown areas in the country. It may occur at any stage of the crop and can cause up to 80% yield loss. The combination of biological control agents viz. Trichoderma harzianum (Th) & Pseudomonas fluorescens (Pf), application of farm yard manure, spent mushroom substrate (SMS) of oyster mushroom and the fungicide (Metalaxyl 8%+Mancozeb 64% WP) were assessed against Phytophthora blight of sesame in terms of incubation period, disease incidence, disease severity and yield under natural epiphytotic field conditions during kharif 2021. Among the treatments assessed, soil application of SMS+Th prior to sowing showed the highest enhancement in terms of incubation period (35.63%) and yield (44.55%) over the control. However, it was at par with respect to the incubation period and yield in the treatment of soil amended with the combination of SMS and (Th+Pf) before sowing. Maximum reduction in disease incidence (20.04%) and severity (51.41%) of Phytophthora blight over the control was recorded in treatments viz., soil amendment with combination of SMS+ (Th+Pf) and SMS+Th, respectively. The results revealed that all the treatments applied as prophylactic treatment, significantly reduced the Phytophthora blight and increased the incubation period and yield over the unprotected crop.